The kinetic model of the combined heterogeneously catalyzed condensation and esterification of propionic acid and methyl propionate with formaldehyde and methanol - Ivasiv, Volodymyr V.; Nebesnyi, Roman V.; Maykova, Svitlana V. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2022)
In this work we aim for developing a kinetic model for the methyl methacrylate and methacrylic acid synthesis by the combined condensation and esterification of methyl propionate and propionic acid with formaldehyde and methanol in the presence of the silica-supported boron-phosphorus-oxide catalyst promoted by oxides of tungsten and zirconium. The dependencies of the formation rates of methyl methacrylate, methacrylic acid and diethyl ketone from the concentrations of methyl propionate, propionic acid, formaldehyde and methanol were studied, and reaction orders of every product formation with respect to each reagent were determined. Methacrylic acid is formed predominantly by condensation of methyl propionate with formaldehyde, and methyl methacrylate hydrolysis is insignificantly. The methyl methacrylate formation reaction rate is limited by the methyl propionate adsorption rate on the catalyst surface, and both reactions of methyl methacrylate and methacrylic acid formation are inhibited due to adsorption of formaldehyde, propionic acid and methanol. Based on obtained data, the reaction scheme was offered, which includes formation of intermediates such as 3-hydroxy-2-methylpropanoic acid, its methyl ester and 3,3-dihydroxy-2-methylpentanoic acid. From this reaction scheme the kinetic model was derived using steady state approximation. The reaction rate constants and their activation energies for this model were calculated from experimental data. Validity of the model was experimentally confirmed by the correlation between experimental and theoretically calculated data. Therefore, the developed kinetic model satisfactorily describes the process of the combined condensation and esterification of methyl propionate and propionic acid with formaldehyde and methanol as well as partial cases of condensation of methyl propionate with formaldehyde and propionic acid with formaldehyde, and is suitable for process optimization and technological calculations.